Repeated-Sprint Performance in Team Sport Players: Associations with Measures of Aerobic Fitness, Metabolic Control and Locomotor Function - Buchheit, M. (International Journal of Sports Medicine, 2012)
To examine the respective associations between indices of aerobic fitness, metabolic control and locomotor function and repeated sprint-performance, 61 team sport players performed: a repeated-sprint sequence (RSS), an incremental test to exhaustion to determine maximal oxygen uptake (V˙O2max) and peak incremental test speed (Inc. test speed), and 2–4 submaximal runs to determine the time constant of the primary phase of V˙O2 kinetics at exercise onset (V˙O2τon) and cessation (V˙O2τoff). The best (RSbest) sprint times and mean sprint times (RSmean) and the percent sprint decrement (%Dec) were calculated. RSmean was almost perfectly correlated with RSbest (r=0.92;90%CL(0.88;0.95)), largely correlated with Inc. test speed (r=−0.71;90%CL(− 0.79; − 0.59)) and moderately correlated with V˙O2max (r= − 0.58;90%CL(− 0.70; − 0.43)); the correlations with V˙O2τon or V˙O2τoff were unclear. For%Dec, the correlations with Inc. test speed, V˙O2max and V˙O2τon were moderate (r=− 0.41;90%CL(− 0.56; − 0.23)), small (r=− 0.26;90%CL(− 0.43; − 0.06)) and small (r=0.28;90%CL(0.09;0.46)), respectively. Stepwise multiple regression analyses showed that the only significant predictors of RSmean were RSbest and Inc. test speed (r2=0.88). Inc. test speed and RSbest were also the only significant predictors of %Dec (r2=0.26). Present results obtained in a large sample of team sport players highlight that locomotor factors (i. e., RSbest and Inc. test speed) show much larger associations with repeated-sprint performance than V˙O2max and V˙O2 kinetics.
Keywords: peak sprinting speed; maximal oxygen uptake; peak incremental test speed; oxygen uptake kinetics; handball; soccer